Transplant rejection and paradigms lost - Strom, Terry B. (American Society for Clinical Investigation, 2013)
During transplant rejection, migrating T cells infiltrate the grafted organ, but the signals that direct this migration are incompletely understood. In this issue of the JCI, Walch et al. debunk two classical paradigms concerning transplant rejection, with important consequences for the design of antirejection therapeutics.